Governance and risk management in taxation - Oliveira Neto, Arnaldo Marques de (Springer, 2017)
This book provides insights into identifying and dealing with possible corporate tax risks. It also elaborates on how enterprises can avoid possible issuance of notices of violation, fines and default interest, and ensure reduced tax responsibility of enterprises and their administrators when dealing with tax issues, thereby bringing about increased efficiency and productivity. Conducted in collaboration with the Brazilian Enterprises Group of Advertising and Publicity Services, it also includes managerial information resources and procedures for tax risks that enterprises may encounter. Additionally, it presents findings that allow the academic community and enterprises (not only advertising and publicity services) alike to benefit from the results derived from the Model of Corporate Risk Management (GRCorp) and the Specific Model of Tax Risk Management (GRTrib) frameworks developed by the author.
Keywords: Corporations -- Taxation -- Accounting.; Corporations -- Taxation -- Brazil.; Taxation -- Law and legislation.; Corporate governance.; Brazil.; elektronické knihy; electronic books